Well-being approaches targeted to improve child and youth health post-COVID-19 pandemic: a scoping review - Stephana Julia Moss; Cynthia Sriskandarajah; Rebecca Brundin-Mather; Michal S. Cherak; Sara J. Mizen; Maia Stelfox; Donna Halperin; Scott Halperin; Sofia B. Ahmed; Diane L. Lorenzetti; Stacie Smith; Micaela Harley; et al. (BMC Health Services Research, 2024)
Abstract Background Our previous work synthesized published studies on well-being interventions during COVID-19. As we move into a post-COVID-19 pandemic period there is a need to comprehensively review published strategies, approaches, and interventions to improve child and youth well-being beyond deleterious impacts experienced during COVID-19. Methods Seven databases were searched from inception to January 2023. Studies were included if they: (1) presented original data on an approach (i.e., approach applied) or (2) provided recommendations to inform development of a future approach (i.e., approach suggested), (3) targeted to mitigate negative impacts of COVID-19 on child and youth (≤18 year) well-being, and (4) published on or after December 2019. Results 39 studies (n = 4/39, 10.3% randomized controlled trials) from 2021 to 2023 were included. Twenty-two studies applied an approach (n = 22/39, 56.4%) whereas seventeen studies (n = 17/39, 43.6%) suggested an approach; youth aged 13–18 year (n = 27/39, 69.2%) were most frequently studied. Approach applied records most frequently adopted an experimental design (n = 11/22, 50.0%), whereas approach suggested records most frequently adopted a cross-sectional design (n = 13/22, 59.1%). The most frequently reported outcomes related to good health and optimum nutrition (n = 28/39, 71.8%), followed by connectedness (n = 22/39, 56.4%), learning, competence, education, skills, and employability (n = 18/39, 46.1%), and agency and resilience (n = 16/39, 41.0%). Conclusions The rapid onset and unpredictability of COVID-19 precluded meaningful engagement of children and youth in strategy development despite widespread recognition that early engagement can enhance usefulness and acceptability of interventions. Published or recommended strategies were most frequently targeted to improve connectedness, belonging, and socialization among children and youth.